1994
DOI: 10.3171/jns.1994.81.5.0699
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after laminectomy for lumbar spinal stenosis

Abstract: All patients who underwent decompressive lumbar laminectomy in the Washtenaw County, Michigan metropolitan area during a 7-year period were studied for the purpose of defining long-term outcome, clinical correlations, and the need for subsequent fusion. Outcome was determined by questionnaire and physical examination from a cohort of 119 patients with an average follow-up evaluation interval of 4.6 years. Patients graded their outcome as much improved (37%), somewhat improved (29%), unchanged (17%), somewhat w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 35 publications
2
56
0
4
Order By: Relevance
“…Several recent, well-designed studies underscore the need for more effective treatments and outcome measures. [18,39,40,51,[68][69][70] Katz and associates [39] prospectively studied 194 patients treated with decompressive laminectomy for degenerative lumbar stenosis and reported that 22% of patients were somewhat or very dissatisfied with the results of surgery 6 months postoperatively. McCullen, et al, [50] reviewing 118 patients who underwent lumbar decompression for acquired spinal stenosis, reported 50% good, 27% fair, and 23% poor outcomes with an overall reoperation rate of 9%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent, well-designed studies underscore the need for more effective treatments and outcome measures. [18,39,40,51,[68][69][70] Katz and associates [39] prospectively studied 194 patients treated with decompressive laminectomy for degenerative lumbar stenosis and reported that 22% of patients were somewhat or very dissatisfied with the results of surgery 6 months postoperatively. McCullen, et al, [50] reviewing 118 patients who underwent lumbar decompression for acquired spinal stenosis, reported 50% good, 27% fair, and 23% poor outcomes with an overall reoperation rate of 9%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preoperative spondylolisthesis as well as progressive postoperative slippage clearly predisposed to poor outcome. Tuite and coworkers [68,69] reviewed 119 patients treated by decompressive lumbar laminectomy and found 66% good outcomes and 34% bad outcomes with a 15% reoperation rate. They also reported that surgical levels undergoing laminectomy were significantly more likely to develop progressive spinal deformity, including progressive spondylolisthesis, disc space angulation, and decreased disc space height.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unilateral decompression by partial hemi laminectomy method of decompression is thought to avoid one side of paraspinal muscle damage and extensor weakness by preserving the attachment of paraspinal muscle less and the posterior l, ligamentous attachments of spinous processes. 7 We present the prospective randomized control study comparing the outcome of a unilateral decompression by partial hemi laminectomy and conventional midline decompression (CMD) by laminectomy in 41 patients who underwent surgery for lumbar spinal canal stenosis. 8 …”
Section: Introductionmentioning
confidence: 99%